2021
DOI: 10.3390/cells10102757
|View full text |Cite
|
Sign up to set email alerts
|

Novel Balance Mechanism Participates in Stem Cell Therapy to Alleviate Neuropathology and Cognitive Impairment in Animal Models with Alzheimer’s Disease

Abstract: Stem cell therapy improves memory loss and cognitive deficits in animal models with Alzheimer’s disease. The underlying mechanism remains to be determined, but it may involve the interaction of stem cells with hippocampal cells. The transplantation of stem cells alters the pathological state and establishes a novel balance based on multiple signaling pathways. The new balance mechanism is regulated by various autocrine and paracrine cytokines, including signal molecules that target (a) cell growth and death. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 131 publications
(162 reference statements)
0
3
0
Order By: Relevance
“…It is noteworthy here that MSCs were previously reported to promote neurogenesis through upregulation of various neurotrophic factors 66,79,80 . NGF is one of these neurotrophins; it promotes neuronal proliferation and neuroprotection 81 . Its decline has been reported to be responsible for cholinergic dysfunction in AD 82 .…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…It is noteworthy here that MSCs were previously reported to promote neurogenesis through upregulation of various neurotrophic factors 66,79,80 . NGF is one of these neurotrophins; it promotes neuronal proliferation and neuroprotection 81 . Its decline has been reported to be responsible for cholinergic dysfunction in AD 82 .…”
Section: Discussionmentioning
confidence: 86%
“…66,79,80 NGF is one of these neurotrophins; it promotes neuronal proliferation and neuroprotection. 81 Its decline has been reported to be responsible for cholinergic dysfunction in AD. 82 In the current study, we found significantly lower NGF expression levels, both in the hippocampus and frontal cortex brain areas.…”
Section: Discussionmentioning
confidence: 99%
“…Transplanted bone marrow-derived mesenchymal stem cells (BMMSCs) stimulate neurogenesis and inhibit apoptosis, regulated by crosstalk between apoptosis and autophagy ( Qin et al, 2021a ). BMMSCs can activate autophagy by increasing the expression of BECN1/Beclin-1 and LC3-II-positive autophagosomes in the hippocampus of APP/PS1 mice, thereby ameliorating Aβ accumulation, hyperphosphorylated tau pathology, and cognitive deficits ( Qin et al, 2021b ).…”
Section: Targeting Autophagy In the Treatment Of Ad Modelsmentioning
confidence: 99%
“…НСК, сверхэкспрессирующие холинацетилтрансферазу, могут обратить вспять пространственную память и дефицит обучения [33]. Основные механизмы связаны с паракринным высвобождением нейропротекторных факторов, ослаблением смешанной протеинопатии (амилоидной и тау), иммуномодуляцией, ингибированием нейровоспаления и усилением нейрогенеза и синаптогенеза [23,34]. Однако присутствуют и проблемы использования трансплантации НСК: они могут в том числе дифференцироваться в ненейрональную глию, возможен туморогенез, используются такие пути введения, как внутригиппокампальная или внутрижелудочковая стереотаксическая инъекция, что является нежелательным явлением, особенно при нескольких применениях.…”
Section:  обзор терапии стволовыми клетками при болезни альцгеймераunclassified
“…На данном этапе лечение лишь симптоматическое и базируется на ингибиторах ацетилхолинэстеразы, таких как донепезил, галантамин, ривастигмин и такрин, антагонисте рецептора N-метил-d-аспартата (NMDA), таком как мемантин, и на Aβ-направленном моноклональном антителе, таком как адуканумаб [19][20][21].  РЕЗУЛЬТАТЫ С помощью стратегии поиска определено шесть связанных статей [23,34,58,62,87]. Четыре дополнительных исследования было выявлено из других источников (поисковая система Google) [11,29,37].…”
unclassified